Extraction, Purification, Composition and Quality Deterioration of Fish Body Oil Extracted From Sardinella Fimbriata by Traditional Method - Sunithadas, K. Gowtham,S. Shanker, E. Anandganesh, A.R. Nazar, G. Marichamy (International Journal of Innovative Research in Medical Science, 2016)
The extraction, refining and evaluation of fish oil from Sardinella fimbriata by Traditional method has been conducted in this work. The total percentage oil yield was 13.5% and the yield after purification was 58%. The analytical properties of the crude and the refined oil were evaluated and it was observed that the crude oil consist from: specific gravity 0.9036, refractive index 1.461, moisture content 0.7%, free fatty acid value 2.9 mg/KOH, iodine value 188 I2/100g, peroxide value 2.18 mEq/kg, saponification value 202.7 mgKOH/g and slight brownish colour. The refined oil was also evaluated as follows: specific gravity 0.8987, refractive index 1.465, moisture content 0.32%,free fatty acid value 2.1 mg/KOH, iodine value 181 I2 /100g, peroxide 1.21 meq/kg, saponification value 174.8 mg KOH/g, and bright yellow colour. The predominant fatty acids found in crude and refined oil were C14:0, C15:0, C16:0, C17:0, C18:0, C23:0, C14:1ω-4, C18:1ω-9, C18:2ω-6, C18:3ω-3, C20:4ω-6, C20:5ω-3, C22:5ω-3 and C22:6ω-3. The total n-3 fatty acid content of the purified catfish oil was 13.361 mg/g of oil. The purified oil contained 5.009 mg/g DHA and 1.173 mg/g EPA. All the essential amino acids were present in the crude fish oil ranged from 1.907 to 0.067µg/g. After purification the major amino acid present was Valine (2.07µg/g) and Threonine (1.26µg/g). The vitamins present were in minor quantities; 0.06, 0.005 and 0.002µg/g of vitamin A, D and E, respectively in crude fish oil. In refined fish oil; 0.04 and 0.003µg/g of vitamin A and D were present.